Using machine learning on a diverse class of problems : from rainfall to criminal actions - Munira, Sirajum; Roy, Tonmona Tonny; Rahman, Tasmia; Javed, Md.Aquib (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.